1995
DOI: 10.1111/j.1365-2125.1995.tb05801.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of rilmenidine and atenolol on mental stress, dynamic exercise and autonomic function in mild to moderate hypertension.

Abstract: 1 The effects of 4 week treatment with rilmenidine or atenolol on tests of mental stress, dynamic exercise, autonomic function and psychometric tests were evaluated in a randomized, double-blind, placebo-controlled, cross-over study. Keywords rilmenidine atenolol hypertension mental stress dynamic exercise autonomic function psychomotor tests Introduction an equivalent efficacy of rilmenidine and a satisfactory safety profile. These comparisons have revealed minimal Rilmenidine is an oxazoline derivative and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…To our knowledge, no study has investigated previously the role of I 1 -imidazoline receptor agonists at low doses on the hemodynamic responses to stress. It has been shown previously that chronic treatment of hypertensive patients with therapeutic doses of rilmenidine (1-2 mg/day) not only caused rest hypotension, but also, inhibited blood pressure increase during mental stress and physical exercise [27]. It is noteworthy that the potential cardioprotective effects of rilmenidine shown in the above mentioned study can also be obtained with lower doses of the drug than the ones used to treat hypertension, as observed in the present study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…To our knowledge, no study has investigated previously the role of I 1 -imidazoline receptor agonists at low doses on the hemodynamic responses to stress. It has been shown previously that chronic treatment of hypertensive patients with therapeutic doses of rilmenidine (1-2 mg/day) not only caused rest hypotension, but also, inhibited blood pressure increase during mental stress and physical exercise [27]. It is noteworthy that the potential cardioprotective effects of rilmenidine shown in the above mentioned study can also be obtained with lower doses of the drug than the ones used to treat hypertension, as observed in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, drugs able to counteract augmented sympathetic activity are potentially useful in this clinical scenario. Panfilov et al [27] compared the effects of rilmenidine and atenolol in hypertensive patients during physical and mental stress and found that these drugs exert comparable antihypertensive effects both at rest and during mental stress and dynamic exercise. However it is not known whether rilmenidine, at a dose lower than the ones recommended for the treatment of hypertension, could inhibit the hemodynamic response to stress.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, it should be remembered that the basal levels of RSNA (or those reached during stress) were still very much lower than those observed in vehicle treated (hypertensive) rabbits. Previous studies have also shown little effect of rilmenidine on the cardiovascular responses to mental stress in hypertensive and normotensive humans [50,51]. However, administration of another centrally acting antihypertensive agent, clonidine, reduced the autonomic response to airjet stress as indicated by changes in medium frequency oscillations [52] and abolished the increased RSNA response to airjet stress in hypertensive conscious rats [53].…”
Section: Effect Of Rilmenidine On Baroreflexes During Stress and Hypementioning
confidence: 93%
“…Previous studies showed no effect of rilmenidine on the cardiovascular responses to mental stress in normotensive and hypertensive humans. 25,26 However, administration of another centrally acting antihypertensive agent, clonidine, reduced the autonomic response to air-jet stress as indicated by changes in medium frequency oscillations 27 and abolished the increased RSNA response to air-jet stress in hypertensive conscious rats. 28 Both of these studies are consistent with our observations that rilmenidine attenuates the sympatho-activation to air-jet stress.…”
Section: Head and Burke Sympathetic Responses In Hypertensive Rabbitsmentioning
confidence: 99%